1978
DOI: 10.1515/cclm.1978.16.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Additional Precipitation Reactions of Lectins with Human Serum Glycoproteins

Abstract: Summary: Highly purified human serum glycoproteins were treated with neuraminidase and examined for their cross reaction with several lectins with anti-galactosyl specificity: )3-.D-galactosyl structures are thought to be the main terminal sugar residues that become attached de novo after removal of neuraminic acid. The following lectins were tested: Tridacnin from the bivalve clams Tridacna maxima and Tridacna gigas, the agglutinin from the sponge Axinella polypoides 9 the lectin from the roach Rutilus rutilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

1978
1978
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…The a1M has a high affinity to polyanions , for example CM-cellulose, agar or heparin and interacts with IgG to a variable extent in the presence of calcium (Cooper and Ziccardi , 1979). Uhlenbruck et al (1978) have observed a totally unexpected precipitationreaction between a1M and asialoceruloplasmin. With regard to galactans a1M shows a calcium-dependent, lectin-like property (Uhlenbruck et al ., 1978).…”
Section: 5s Al-glyco Proteinmentioning
confidence: 89%
See 1 more Smart Citation
“…The a1M has a high affinity to polyanions , for example CM-cellulose, agar or heparin and interacts with IgG to a variable extent in the presence of calcium (Cooper and Ziccardi , 1979). Uhlenbruck et al (1978) have observed a totally unexpected precipitationreaction between a1M and asialoceruloplasmin. With regard to galactans a1M shows a calcium-dependent, lectin-like property (Uhlenbruck et al ., 1978).…”
Section: 5s Al-glyco Proteinmentioning
confidence: 89%
“…Uhlenbruck et al (1978) have observed a totally unexpected precipitationreaction between a1M and asialoceruloplasmin. With regard to galactans a1M shows a calcium-dependent, lectin-like property (Uhlenbruck et al ., 1978).…”
Section: 5s Al-glyco Proteinmentioning
confidence: 89%
“…The IgE VL has demonstrated a very high precipitating activity with all mannose-specific lectins [9] without usu ally necessary neuraminidase treatment [21]. Only 3 lectins did not show positive reaction: soybean, V. cracca and V villosa, all carrying higher specificity for D-GalNAc.…”
Section: Precipitating Activity O F Ige Vl With Lectinsmentioning
confidence: 96%
“…The reactions with carbohydrate-containing polymers and serum glycoproteins have also been investigated and concanavalin A (con A), the Jack Bean lectin, which has a specific affinity for a-D-glucosyl residues and sterically related structures, has been found to bind and precipitate serum proteins including the acute phase reactants [3,4]. However, no attention has been paid to the value of lectin-serum glycoprotein interaction for the assessment of the biological response to physiological, pathological and 'pharmacological' agents.…”
Section: Introductionmentioning
confidence: 99%